Dielectric Polarization and Particle Shape Effects. (25th June 2007) - Sihvola, Ari
Abstract : This article reviews polarizability properties of particles and clusters. Especially the effect of surface geometry is given attention. The important parameter of normalized dipolarizability is studied as function of the permittivity and the shape of the surface of the particle. For nonsymmetric particles, the quantity under interest is the average of the three polarizability dyadic eigenvalues. The normalized polarizability, although different for different shapes, has certain universal characteristics independent of the inclusion form. The canonical shapes (sphere, spheroids, ellipsoids, regular polyhedra, circular cylinder, semisphere, double sphere) are studied as well as the correlation of surface parameters with salient polarizability properties. These geometrical and surface parameters are essential in the material modeling problems in the nanoscale.